WRITTEN MATHEMATICAL COMMUNICATION SKILLS ON OPEN-ENDED PROBLEMS: IS IT DIFFERENT BASED ON THE LEVEL OF MATHEMATICS ABILITY? - Septi Dariyatul Aini; Moh. Zayyadi; Kuratul Aini Saleh (Department of Mathematics Education Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2020)
This study aims to describe students' written mathematical communication skills in open-ended problems based on their mathematical abilities. This research was conducted at grade VII-A of SMPN 1 Pamekasan. This research uses descriptive qualitative research. The instruments used were the Mathematical Ability Test (MAT), Written Mathematical Communication Skills Test (WMCST) on open-ended problems, and Interview Guidelines. The results showed that subjects with high and moderate mathematical ability were able to meet three indicators of written mathematical communication skills, namely being able to express mathematical ideas through writing, demonstrate and convey visually; able to understand, interpret and evaluate mathematical ideas in writing, as well as in other visual forms; and able to use mathematical notations in the structure to write down ideas and relationships with situation models in writing. Meanwhile, subjects with low mathematics ability can fulfill 2 out of 3 indicators of written mathematical communication skills, namely being able to express mathematical ideas through writing, demonstrate and convey visually; unable to understand, interpret and evaluate mathematical ideas in writing or other visual forms; and able to use mathematical notations in the structure to write ideas and relationships with situation models.